2017
DOI: 10.1016/j.tibs.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Hippo Pathway Transcription Factor TEAD

Abstract: The TEAD transcription factor family is best known for transcriptional output of the Hippo signaling pathway and has been implicated in processes such as development, cell growth and proliferation, tissue homeostasis, and regeneration. Our understanding of the functional importance of TEADs has increased dramatically since its initial discovery three decades ago. The majority of our knowledge of TEADs is in the context of Hippo signaling as nuclear DNA binding proteins passively activated by YAP and TAZ, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
206
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(229 citation statements)
references
References 90 publications
7
206
0
3
Order By: Relevance
“…These findings were similar to those in recent reports which showed that WBP2 can directly interact with or affect YAP through WW domains [18][19][20]. The TEA domain (TEAD) family of transcription factors (TEAD1-4) play an important role in tumorigenesis by regulating various cellular processes, including cell growth, proliferation, differentiation, and survival [21]. YAP in conjunction with TEAD1-4 mediate major physiological functions of the Hippo pathway [22,23].…”
Section: Discussionsupporting
confidence: 90%
“…These findings were similar to those in recent reports which showed that WBP2 can directly interact with or affect YAP through WW domains [18][19][20]. The TEA domain (TEAD) family of transcription factors (TEAD1-4) play an important role in tumorigenesis by regulating various cellular processes, including cell growth, proliferation, differentiation, and survival [21]. YAP in conjunction with TEAD1-4 mediate major physiological functions of the Hippo pathway [22,23].…”
Section: Discussionsupporting
confidence: 90%
“…TEADs are DNA‐binding proteins that can be activated by YAP1 and work as transcription factors . YAP1 has been demonstrated to promote tumorigenesis by activating TEAD in breast cancers, cholangiocarcinoma, and renal cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…When not phosphorylated by the Hippo core cassette, YAP/TAZ/ Yki translocate to the nucleus and associate with transcriptional regulators including those of the TEAD family to induce gene expression (Lin et al 2017). Consequently, Hippo pathway activity inhibits YAP/TAZ/Yki target gene expression.…”
Section: Rhobtb Lkb1 (Stk11) Hippo Pathway Ubiquitinationmentioning
confidence: 99%